Beckett's Intuitive Spectator Me to Play - Chiang, Michelle (New Interpretations of Beckett in the Twenty-First Century, 2018)
Beckett's Intuitive Spectator: Me to Play investigates how audience discomfort, instead of a side effect of a Beckett pedagogy, is a key spectatorial experience which arises from an everyman intuition of loss. With reference to selected works by Henri Bergson, Immanuel Kant and Gilles Deleuze, this book charts the processes of how an audience member's habitual way of understanding could be frustrated by Beckett's film, radio, stage and television plays. Michelle Chiang explores the ways in which Beckett exploited these mediums to reconstitute an audience response derived from intuition. .